Розробка цілісного користувацького досвіду для криптовалютного сервісу: важливість мобільного додатку - Дудка, С. А. (ХНУРЕ, 2025)
This work focuses on the significance of UI/UX design in cryptocurrency mobile applications, emphasizing intuitive navigation, security, and transaction efficiency. As competition grows, a well-structured interface is crucial for user retention. It highlights key challenges, such as complex navigation and security concerns, and proposes solutions through optimized UX strategies. The work examines usability testing, fraud prevention mechanisms, and interactive onboarding to enhance user trust. Implementing a comprehensive UI/UX approach ensures accessibility, security, and a seamless user experience.
Keywords: криптовалютний сервіс; важливість мобільного додатку